Mapping Forestry Suitability Land and Landuse in the Highland, Usumacinta Watershed, Mexico - Daniel, M. López L.; Aristides, Saavedra G (European Journal of Applied Sciences, 2024)
The Usumacinta Watershed is a trans-boundary basin shared by Mexico, Guatemala, and Belize. It is one of the ecosystems of great importance with a diversity of habitats and species, many of them unique to this area. In the last decades, the anthropic pressure have exerted on natural ecosystems and land dedicated to productive activities has been increasing, causing intense negative environmental effects on soil, water, flora and fauna resources, as well as on the ecosystems services that this ecosystem provide. It is the objective of this paper mapping and analyze the forest land suitability and its present land use. Base of land suitability, the forest land suitability were defined, grouping it in three classes: f1- forest land, slope 12-25%, f-2 Forest land, slope 25-50%, and f3- forest land, slope >50%; by overlay these classes with present land use, the area occupied for each one of land-use was defined ; besides considering the natural protected areas, the proportion that occur inside and outside of this area was defined.From the results can be draw that the forest land suitability in the upland area of Usumacinta watershed occupied an important extension ( 61.45%) of total area, being group ”f2- 25-50%”, the dominant; the most part of conserved forest areas are inside of natural protected areas. Nevertheless, outside of protected areas there are considerable areas of land forest (according to land suitability) where the natural vegetation, because antropic pressure, has been replaced to secondary vegetation, grasslands and crops; because of high environmental risk of these uses, they must be considered in a program to recovery the natural vegetation for conservation and protection of soils, water and forests resources.